GAMBARAN KETERPAPARAN MEDIA INFORMASI TERHADAP TINDAKAN SEKS PRA NIKAH PADA MAHASISWA INDEKOST KAMPUNG SUSUK KELURAHAN PADANG BULAN SELAYANG 1 KECAMATAN MEDAN SELAYANG KOTA MEDAN TAHUN 2014 - myke rumapea; Lita Sri Andayani; eddy syahrial (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2015)
Information technology is evolving in bulk, has changed the shape of society, from the local people of the world into a global world community. Social changes as a result of the fast-paced process of modernization and globalization has resulted in changes in the pattern of life, ethics and moral values ​​in particular the relationship of sexual behavior. Students as part of the community is a great consumer of media information, whether in print, and electronic media. This study aims to describe the information media exposure to premarital sexual acts boarding student at Kampung Susuk, Medan 2014. This is a descriptive study with a qualitative approach, with the aim to determine the effect of media exposure information on premarital sexual acts boarding student at Kampung Susuk Medan Year 2013. The method used was to interview the informant chosen in Kampung Implant. The number of informants in this study 5 people. Boarding students at Kampung Susuk understand what media information and feel increased knowledge of sexual information through the media. This gives the effect on the sexual attitudes of students boarding that arouse sexual desire in themselves and to give effect to their sexual actions, evident from their sexual activity with a partner. Therefore, the necessary existence of clear rules about visiting hours, and a ban on bringing a friend of the opposite sex to stay at the boarding house with clear sanctions against the perpetrators as well as the commitment of the residents who live for obey it. It also need a serious attention from the local community, both from the head of the environment and security forces against the sexual behavior of children in boarding house, for example by sharing a circular letter to the owners and occupants of the boarding house.